Calcium Signaling Mediates Cell Death and Crosstalk with Autophagy in Kidney Disease - Bo Ning (MDPI AG, 2021)
The kidney is an important organ for the maintenance of Ca2+ homeostasis in the body. However, disruption of Ca2+ homeostasis will cause a series of kidney diseases, such as acute kidney injury (AKI), chronic kidney disease (CKD), renal ischemia/reperfusion (I/R) injury, autosomal dominant polycystic kidney disease (ADPKD), podocytopathy, and diabetic nephropathy. During the progression of kidney disease, Ca2+ signaling plays key roles in various cell activities such as necrosis, apoptosis, eryptosis and autophagy. Importantly, there are complex Ca2+ flux networks between the endoplasmic reticulum (ER), mitochondria and lysosomes which regulate intracellular Ca2+ signaling in renal cells and contribute to kidney disease. In addition, Ca2+ signaling also links the crosstalk between various cell deaths and autophagy under the stress of heavy metals or high glucose. In this regard, we present a review of Ca2+ signaling in cell death and crosstalk with autophagy and its potential as a therapeutic target for the development of new and efficient drugs against kidney diseases.